Integrating political prioritisation into national surgical planning: a scoping review of surgical, obstetric and anaesthesia care in Cameroon - Sara Fewer; Melissa Carvalho; Catherine Juillard; Rasheedat Oke; Alain Mballa Etoundi; Lauren Agoubi; Brice Fabo; Leonid Daya; Fiona Obiezu; Janet Adeola; Boris A K Nteungue; Yannick Ekane (BMJ Global Health)
Background Surgical diseases contribute substantially to death and disability in Cameroon. Strategic planning for surgical, obstetric and anaesthesia (SOA) care in low-income and middle-income countries (LMICs) requires consideration of the policy environment in addition to the issue severity. We aimed at the current landscape of SOA care in Cameroon, incorporating a framework for political prioritisation.Methods A scoping review of published and grey literature was performed. Literature specific to Cameroon, published between 2010 and 2020 and written in either English or French, was included. Abstracts and full texts were screened for discussion of SOA policy context, care and delivery conditions, and issue characteristics. Data extraction and analysis were performed using the Shiffman and Smith framework for political prioritisation accounting for actors, ideas, political context and issue characteristics.Results 121 articles were included. By specialty, 83 articles were specific to surgery, 45 to obstetrics and 6 to anaesthesia. Policy environment was discussed by 20% (n=25) articles; 30% (n=37) discussed actor power; 22% (n=27) discussed ideas in SOA care and 93% discussed issue characteristics. Core challenges to political prioritisation of SOA care in Cameroon are limited actor support, a lack of consensus definitions, gaps in capacity and a need for systematic data collection on surgical diseases. Policy opportunities include leveraging existing multilateral partnerships to unify SOA actors, conducting national assessments of SOA care capacity, formalisation of task shifting to build capacity, defining essential SOA procedures, including surgical care in future health coverage, and defining and including SOA benchmarks in strategic planning.Conclusions Integrating a framework for political prioritisation into a situational analysis of SOA care is critical to understanding an LMIC’s policy context and actors, in addition to issue severity. Such an approach can serve as a baseline for analysis in evidence-informed policy-making for SOA care, even in the absence of centralised, country-wide data.